(untitled) (Research, Society and Development, 2020)
Strategies related to marketing have stood out today for providing the narrowing of the company-consumer relationship, as a result of the adoption of actions that reinforce the company’s differential, its products and attributes to the customer, through promotions, disclosures and price, with emphasis on the use of digital media. In this sense, this research aims to describe the process of developing and implementing a promotional strategy focusing on the use of digital media for the agribusiness Leves Castanhas Ltda. The company is located in the municipality of Iporá, founded in 2015, becoming a reference in the processing and commercialization of chestnuts. The agribusiness has a staff of twelve (12) employees who are directly linked to the processing of nuts, providing customers with a diversified product mix including, Brazil nuts, cashew nuts and barú nuts. The research is classified as quali-quantitative in terms of its nature and exploratory and descriptive in terms of objectives, with a literature review, document analysis and survey of tools provided by Instagram being adopted. The analysis of the results reinforces the importance of using social media, differentiated packaging and marketing strategies to increase the reach of a company to its target audience, in addition to helping the entrepreneur himself to discover ways on how to improve his product, presenting to his collaborators information such as age group, main cities that buy your products, the genre you buy the most, thus being able to differentiate more and more the products offered.